24‐3: An 8.34‐inch 1058‐ppi 8K x 4K Flexible OLED Display. Issue 1 (May 2017) - Aoyama, Tomoya; Yamazaki, Ikumi; Shiokawa, Masataka; Toyotaka, Kouhei; Nagata, Takaaki; Jimbo, Yasuhiro; Shishido, Hideaki; Yokoyama, Kohei; Ikeda, Hisao; Eguchi, Shingo; Yamazaki, Shunpei; Misawa, Chieko; et al.
Abstract : We have successfully fabricated an 8.34‐inch 1058‐ppi 8K x 4K flexible organic light‐emitting diode (OLED) display. It exhibits the world's highest resolution and pixel density among flexible OLED displays, offering excellent viewing‐angle characteristics owing to the arrangement of subpixels in a zigzag pattern.